DICTOGLOSS TECHNIQUE TO TEACH STUDENTS’ LITERAL LISTENING IN EFL CONTEXT - Lucky Rahayu nurjamin (Institut Pendidikan Indonesia Garut, 2019)
The communication used in our real life situation spent 45% involvement of listening activity (Feyten; 1991). This big involvement of listening skill triggered the theorist to extent the method in teaching listening. In order to make an extension of teaching listening, thus, this study was undertaken. This study investigated the effectiveness of dictogloss technique in teaching studentsâ€™ literal listening. Quantitative approach used pre-experiment study was chosen to examine the method. The research site in this study is the first semester of university students, particularly 40 students were chosen as participants of the study.Â